Namal Institute: A Mission for Rural Uplift, Sustainable Development, and Social Impact - Riaz, Yasir (Universitas Diponegoro, 2021)
Namal Institute was established by Mr. Imran Khan, a famous philanthropist and the current Prime Minister of Pakistan, with a mission for rural uplift and development through educating bright youth and offering innovative solutions to rural challenges through research by highly trained academics. The majority of the Namal’s students belong to rural areas, and 97% of them secured scholarship either due to meritorious educational background or being unable to afford education (i.e., needbased scholarship). To ensure quality, Namal has kept a student-faculty ratio of 10:1. It is one of the pioneering institutes focusing on Agribusiness and Agri-tech education in Pakistan. It has a beautiful campus comprising of 1000 Acres land located in the Salt Range in an area consisting of hills and crags overlooking Namal Lake in the Mianwali District. To foster its sustainability efforts, Namal has planted an olive garden on an area of 4 acres. Recently, two new blocks have been constructed using environmentfriendly material (e.g., mud blocks, solar-powered LED lights, etc.). Various student societies in Namal Institute have also taken different environmental and social initiatives in the rural area. Primarily during the corona pandemic, the Namal Society for Social Impact (NSSI) has managed to deliver ration packages to the deserving low-income families of the rural area. The medical and administrative staff has distributed essential protection material to the hospitals/doctors in the rural area.